دور الثقافة التنظيمية على متغيرات الابداع الإداري في المنظمات العامة دراسة تطبيقية على الإدارتين الوسطى والدنيا في مصفاة الزاوية (Comprehensive Journal of Science, 2025)
This study examines how organizational culture fosters managerial creativity in public organizations, using a field application on middle and lower management at the Zawiya Refinery. The population comprised 145 employees; analysis relied on 137 valid Likert-scale questionnaires. The instrument showed high reliability (Cronbach’s alpha = 0.94). Descriptively, culture was positive in shared values, supportive norms, and performance expectations, with relative weaknesses in incentives, risk tolerance, and empowerment. For creativity, flexibility, problem sensitivity, and originality were high, whereas idea fluency and risk-taking were moderate. Inferentially, organizational culture correlated strongly and positively with managerial creativity (r = 0.68, p < 0.01). Significant differences favored middle management in both culture and creativity assessments. Recommendations include linking rewards to innovation, expanding delegation, adopting “calculated risk-taking,” strengthening feedback channels, and enhancing training on problem-solving and creativity. The findings guide decision-makers to translate positive cultural orientations into concrete practices that sustain innovation.
Keywords: Organizational culture; Managerial creativity; Zawiya Refinery; Cronbach’s alpha; Pearson correlation; Incentives; Empowerment; Calculated risk.